BcNRAMP1 promotes the absorption of cadmium and manganese in Arabidopsis. (November 2021) - Yue, Xiaomeng; Song, Jinxue; Fang, Bo; Wang, Lu; Zou, Jianwen; Su, Nana; Cui, Jin
Abstract: Cadmium (Cd) is a toxic nonessential metal that poses a health risk for humans. Cd is easily accumulated in leaf vegetables than in other vegetables. Leafy vegetables are one of the major dietary Cd sources for the human body. In this study, pak choi was used as our experimental material as it is an important leafy vegetable, especially in Asia. A NRAMP transporter – BcNRAMP1 was identified in pak choi, which is involved in manganese (Mn) and Cd uptake in yeast and in planta . BcNRAMP1 is expressed in the whole plant body of pak choi, with a higher abundance in root tissues than in shoots. Mn deficiency and Cd exposure strongly induced BcNRAMP1 transcription levels. Through transient expression of BcNRAMP1-GFP fusion protein in tobacco leaf epidermal cells, BcNRAMP1 was revealed as a plasma membrane protein. Expressing BcNRAMP1 in yeast enhanced yeast cells to absorb Mn, Cd, and iron (Fe). Overexpression of BcNRAMP1 in Arabidopsis wild-type and nramp1 mutant increased and complemented Mn and Cd transportation and accumulation, respectively. Using noninvasive microelectrode ion flux measurements, a direct evidence that BcNRAMP1 acts on Cd influx in Arabidopsis root cells was provided. The results of this study reveal that BcNRAMP1 functions as a NRAMP protein in planta, absorbing nutrient metal Mn and the toxic metal Cd. Highlights: BcNRAMP1 had Cd, Mn, and iron (Fe) transport activities in yeast mutants. Subcellular localization indicated that BcNRAMP1 was a plasma membrane protein. BcNRAMP1 expressed the activity to accumulate Cd and Mn in Arabidopsis. NMT recognized that BcNRAMP1 acts on Cd influx in Arabidopsis root cells.